Face to face with COVID-19: highlights of challenges encountered in various ENT practices across the Czech Republic (a national survey) - Guha, Anasuya (Eur Arch Otorhinolaryngol, 2020)
The SARS-CoV-2 virus causing the COVID-19 disease created considerable complications and disruptions due to it's pandemic spread. The nature of the disease left certain clinical specialties more vulnerable than others, causing serious problems with organization of care of patients. Most studies concentrated on protocols and strategies to control the situation and reduce further spread amongst medical fields. Only few were designed to identify the various issues faced by doctors. We decided to design a questionnaire addressing relevant matters for doctors working in the field of ear, nose and throat (ENT). This was then sent to all the members of the Czech Society of Otorhinolaryngology. All ENT doctors were invited to fill out the survey within a stipulated time. The aim of the study was to evaluate the impact of a pandemic situation amongst such a high risk specialty. Our results showed a significant difference between the first cases of COVID-19 and progress of the disease during April 2020 in terms of workplace preparation, adequacy of personal protective equipment and other disposable aids. There was also inadequate support of medical personnel within the ENT practices. Furthermore, financial losses were also experienced due to mainly patient-related problems. In conclusion, the obtained results were used to formulate some recommendations for the public, patients, medical staff and employers. These suggestions will hopefully help avoid a repetition of the glitches if faced with another pandemic situation.